Nicotinamide: a vitamin able to shift macrophage differentiation toward macrophages with restricted inflammatory features. - Weiss, R.; Schilling, E.; Grahnert, A.; Kolling, V.; Dorow, J.; Ceglarek, U.; Sack, U.; Hauschildt, S. (Innate Immun, 2015)
The differentiation of human monocytes into macrophages is influenced by environmental signals. Here we asked in how far nicotinamide (NAM), a vitamin B3 derivative known to play a major role in nicotinamide adenine dinucleotide (NAD)-mediated signaling events, is able to modulate monocyte differentiation into macrophages developed in the presence of granulocyte macrophage colony-stimulating factor (GM-MO) or macrophage colony-stimulating factor (M-MO). We found that GM-MO undergo biochemical, morphological and functional modifications in response to NAM, whereas M-MO were hardly affected. GM-MO exposed to NAM acquired an M-MO-like structure while the LPS-induced production of pro-inflammatory cytokines and COX-derived eicosanoids were down-regulated. In contrast, NAM had no effect on the production of IL-10 or the cytochrome P450-derived eicosanoids. Administration of NAM enhanced intracellular NAD concentrations; however, it did not prevent the LPS-mediated drain on NAD pools. In search of intracellular molecular targets of NAM known to be involved in LPS-induced cytokine and eicosanoid synthesis, we found NF-kappaB activity to be diminished. In conclusion, our data show that vitamin B3, when present during the differentiation of monocytes into GM-MO, interferes with biochemical pathways resulting in strongly reduced pro-inflammatory features.
Keywords: Cell Differentiation/drug effects; Cells, Cultured; Eicosanoids/biosynthesis; Gene Expression Regulation/drug effects; *Granulocyte-Macrophage Colony-Stimulating Factor/metabolism; Humans; Inflammation; *Macrophage Colony-Stimulating Factor/metabolism; *Macrophages/cytology/immunology/metabolism; *Monocytes/cytology/immunology/metabolism; NAD; NF-kappa B/metabolism; *Niacinamide/metabolism/pharmacology; Signal Transduction/drug effects; *Vitamin B Complex/metabolism/pharmacology